DEVELOPMENT OF ELECTRONIC STUDENTS’ ACTIVITY SHEETS USING KVISOFT FLIPBOOK MAKER APPLICATION AND A STEM-BASED APPROACH ON HYDROCARBON MATERIALS - Irfandi Irfandi; Aprizal Aprizal; Alhairi Alhairi; Maya Febriani Chandra; Respito Rini (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
Using the Kvisoft Flipbook Maker application, this study seeks to develop an Electronic Student Activity Sheet (e-LKM) based on a STEM (Science Technology Engineering and Mathematics) approach to Hydrocarbon Materials. This research is Research and Development (R and D) employing the Plomp model, which consists of Preliminary Research (introduction), Prototype Stage (development), and Evaluation. Utilizing material and media expert validation sheets, this study's data acquisition method is based on expert validation sheets. The validity of e-LKM was demonstrated by material expert validation of 0.93 and media validity of 0.92 for the appropriate category, as determined by Aiken V analysis. The percentage of material validity results is 94.8 per cent, while the percentage of media with intriguing categories is 93%. The results of user responses from lecturers and students yielded percentages of 87% and 90% for the category